Polymerization catalysis for the precision synthesis of chiral and sustainable polymers - Miyake, Garret M., author; Chen, Eugene, advisor; Bailey, Travis, committee member; Prieto, Amy, committee member; Strauss, Steven, committee member; Wang, David, committee member (Colorado State University. Libraries, 2011)
Polymerization catalysis for the precision synthesis of chiral and sustainable polymers is described in this dissertation. The central theme of chiral polymers has revolved around the employment of newly synthesized enantiomeric zirconocenium ester enolate catalysts. These catalysts have been utilized in the asymmetric coordination polymerization of prochiral functionalized vinyl monomers towards optically-active, solution stable, one-handed helical polymers. These enantiomeric catalysts have also been used in the successful kinetic resolution polymerization of a racemic methacrylamide monomer. The stereospecific polymerization of chiral oxazolidinone functionalized alkenes has been performed, producing highly isotactic polymers that assume helical or random-coil secondary conformations, dictated by the proximity of the chiral oxazolidinone to the main-chain of the polymer. Investigating applications of helical polymers, two pseudo-enantiomeric helical poly(phenyl acetylene)s bearing chiral organocatalyst side-groups have been synthesized and the effects of the helix-sense and helicity on the enantioselectivity of these catalysts was subsequently examined. Towards sustainable polymers, renewable butyrolactone-based vinylidene monomers are of particular interest in exploring the prospects of substituting the petroleum-based methacrylate monomers for specialty chemicals production. The polymerization of such monomers by group III and IV transition metal catalysts has been investigated resulting in the synthesis of sustainable polymers with controlled molecular weights. These butyrolactone-based monomers have also been successfully polymerized in a rapid and living fashion, using ambiphilic silicon propagating species.